Follicular Thyroid Carcinoma Presenting With Endobronchial Metastases - Nduche Chika Onyeaso MBBS; Aidar R. Gosmanov MD, PhD, FACE (SAGE Publishing, 2014)
Endobronchial metastasis is a rare manifestation of differentiated thyroid cancer. A 79-year-old male was admitted to the hospital with shortness of breath, chest pain, anemia, and weight loss. Computed tomography of chest revealed multiple lung nodules. Bronchoscopy showed an endobronchial lesion in the right upper lobe. The biopsy of the lesion demonstrated neoplastic cells stained positive for thyroglobulin, thyroid transcription factor-1, and cytokeratin-7, consistent with metastatic follicular thyroid cancer. Physical examination revealed a firm fixed thyroid nodule, which was confirmed by thyroid ultrasound. He subsequently underwent total thyroidectomy and neck exploration. Thyroid gland pathology revealed a nodule with features of high-grade follicular thyroid carcinoma. Metastatic thyroid cancer should be considered in workup of pulmonary nodules. We recommend an examination of thyroid gland in patients who present with pulmonary nodules associated with signs and symptoms of malignancy.